Corrigendum to “Smarandache Ruled Surfaces according to Frenet-Serret Frame of a Regular Curve in E3” - Soukaina Ouarab (Abstract and Applied Analysis)
In this paper, we introduce original definitions of Smarandache ruled surfaces according to Frenet-Serret frame of a curve in E3. It concerns TN-Smarandache ruled surface, TB-Smarandache ruled surface, and NB-Smarandache ruled surface. We investigate theorems that give necessary and sufficient conditions for those special ruled surfaces to be developable and minimal. Furthermore, we present examples with illustrations.